Recurso educativo digital para mejorar el proceso de enseñanza - aprendizaje en la asignatura de inglés con los estudiantes de sexto año de educación general básica en la escuela de educación básica "Darío c. Guevara" de la parroquia San José del Tambo, cantón Chillanes, provincia Bolívar, durante el periodo lectivo 2022-2023 - Gavilanes Vallejo, Angel Eudoro (2023)
Nowadays, the use of technologies has become a transversal part of people; in the educational sector, the creation of digital educational resources has been promoted in order to strengthen the teaching-learning process. This educational technological proposal was found based on the creation of digital educational resources to optimize the cognitive development of students, specifically in the subject of English, which was implemented to students in the sixth year of General Basic Education of the School of Basic Education “Dario C. Guevara”, using new methodological strategies through the implementation of RED. In order to know the degree of knowledge of the students, a pretest of the subject of English was carried out, in which it was evidenced that there was a deficit of knowledge, for this reason, this technological educational proposal seeks to strengthen learning in this subject. The digital educational resource (RED), was created in the Ardora 9 program, presenting multiple activities that were related to the subject of English for the process of strengthening knowledge, in which it was constituted of interactive playful activities, gamification and multimedia elements. The purpose that was obtained was that the students develop their abilities and linguistic skills. When the digital educational resource was implemented in the experimental group, it was found that thanks to the digital educational resource created, the students of this educational institution significantly improved their learning in the subject of English